Penentuan Volume Batubara Menggunakan Metode Cross Section di PT. Astri Mining Resources Cabang Batu Ampar Kalimantan Selatan - Megawati, Megawati; Wahyono, Sri Cahyo; Fahruddin, Fahruddin (Jurnal Fisika FLUX, 2017)
Coal is a combustible sedimentary rock formed from organic deposits of plant residues and carbon, hydrogen and oxygen elements. Modeling of 3D coal distribution and coal volume calculation plays an important role in the exploration because the result of coal volume calculation can be used as consideration for mining. This research uses 6 drill point and calculation of coal volume using cross section method with the help of image processing software that is rockwork16. The result of interpretation of drill point data in the research area were 5 types of rock layers with each rock volume is claystone (25.840.000 m3), claysand (230.00 m3), Coal (5.930.000 m3), carbonaceus clay and soil.